AI’s Functions and Influences Among University Students in Indonesian Context - Maryansyah , Yupika; Badeni, Badeni; Masito, Fitri (UNIB Press, 2025)
This study explores functions and influences of artificial intelligence (AI) in English language learning among English education and non-English education students. Using semi-structured interviews with 36 students from four universities in Bengkulu, Indonesia, and analyzed through Interpretative Phenomenological Analysis (IPA), the study identifies five key functions of AI: learning booster, flexible learning assistant, personal learning source, virtual teacher, and instant problem solver. Both groups shared similar views on the first three functions, while English education students emphasized AI as a virtual teacher, and non-English education students saw it more as an instant problem solver. Four influence themes emerged: acceleration of English mastery, increased learning motivation, reduced desire for face-to-face conversation, and growing dependency on AI tools. Both groups agreed on the first two, but differed on the latter, English education students noted reduced face-to-face interaction, while non-English education students highlighted dependency on AI. The findings stress the importance of balancing AI use with human interaction to support comprehensive language learning.